2019
DOI: 10.1002/gj.3460
|View full text |Cite
|
Sign up to set email alerts
|

The mafic–ultramafic complex of Salem, southern India: An analogue for Neoproterozoic Alaskan‐type complex

Abstract: The Salem Mafic–Ultramafic Complex occurs within the northern part of Cauvery Suture Zone (CSZ), Southern Granulite Terrane (SGT), India. The complex occurs as semicircular to elongated linear body with a thick mantle section and comparatively well‐developed crustal section comprising different lithological units, also referred to as the Chalk Hills of Salem. The major rock types in the complex comprise ultramafic cumulates of dunite, peridotite, wherlite, pyroxenite, and hornblendite, mafic and felsic intrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 89 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…Our results reveal the presence of a high density mafic crustal unit at the southern margin of the SASZ. The study also reveals spatial as well as vertical extensions of the Salem mafic-ultramafic complex, popularly known as Chalk hill, which is reported to be Alaskan-type complex developed in rift-related setting (Yellappa et al, 2019;He et al, 2015). The present study is leading to propose an accretionary tectonic model across the SASZ.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Our results reveal the presence of a high density mafic crustal unit at the southern margin of the SASZ. The study also reveals spatial as well as vertical extensions of the Salem mafic-ultramafic complex, popularly known as Chalk hill, which is reported to be Alaskan-type complex developed in rift-related setting (Yellappa et al, 2019;He et al, 2015). The present study is leading to propose an accretionary tectonic model across the SASZ.…”
Section: Introductionmentioning
confidence: 54%
“…A diverse sequence of mafic and ultramafic assemblages, gneiss, charnockite, pyroxene granulites, and banded magnetite quartzites are exposed along the SASZ. Majority of the rock types around the SASZ are highly deformed and converted into mylonites (Yellappa et al, 2019). The Sweta Nadi Shear zone, trending in ENE-WSW direction, which is running through the southern part of the study area, reported by Behera et al (2019) but details are not available.…”
Section: Geological Set Up Of Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…WDC, Western Dharwar Craton; EDC, Eastern Dharwar Craton EDC; CG, Closepet Granite; FL, Fermor's line; BRB, Billigiri Rangan Block; MB, Madurai Block; TB, Trivundrum Block; McSZ, Mercara Shear Zone; MSZ, Moyar Shear Zone; BSZ, Bhavani Shear Zone; MBSZ, Moyar Bhavani Shear Zone; MTSZ, Mettur Shear Zone; NLSZ, Nallamalai Shear Zone; SASZ, Salem Attur Shear Zone; PCSZ, Palghat Cauvery Shear Zone; CNSZ, Chennimalai Noyil Shear Zone; DSZ, Dharapuram Shear Zone; DKSZ, Devattur‐Kallimandayam Shear Zone; KOSZ, Karur Oddanchatram Shear Zone; ASZ, Achankovil Shear Zone; 1, Salem Mafic Ultramafic Complex (S MUC); 2, Agalli Hill Ophiolite Complex (AOC); 3, Aniyapuram Mafic Ultramafic Complex (AMUC); 4, Manamedu Ophiolite Complex (MOC); 5, Devanur Ophiolite Complex (DOC). The hatched portion bounded by BSZ, MBSZ, SASZ, and PCSZ in known as Cauvery Shear/Suture Zone (CSZ; map compiled after GSI, 1998; Chetty et al, 2016; Chetty, 2017; Yellappa, Santosh, & Manju, 2019; Li et al, 2018). Rectangular Box indicates study area [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…The Salem mafic–ultramafic Complex occurs within the Southern Granulite Terrane (SGT), India along the trace of a major Neoproterozoic suture zone. Yellappa, Santosh, and Manju (—this issue) present the results from petrological and geochemical studies of this complex. They equate this suite with typical Alaskan‐type complex.…”
mentioning
confidence: 99%